Cultural Attachment: From Behavior to Computational Neuroscience - Yap, Wei-Jie; Cheon, Bobby; Hong, Ying-yi; Christopoulos, George I. (Frontiers in Human Neuroscience, 2019)
Cultural attachment (CA) refers to processes that allow culture and its symbols to provide psychological security when facing threat. Epistemologically, whereas we currently have an adequate predictivist model of CA, it is necessary to prepare for a mechanistic approach that will not only predict, but also explain CA phenomena. Toward that direction, we here first examine the concepts and mechanisms that are the building blocks of both the prototypical maternal attachment as well as CA. Based on existing robust neuroscience models we associate these concepts and mechanisms with bona fide neurobiological functions to advance an integrative neurobiological model of CA. We further discuss the unresolved relationship of CA to other similar socio-cognitive concepts such as familiarity. Overall aim of the paper is to highlight the importance of integrating CA theory to computational approaches to culture and evolution (such as predictive processing computations explaining niche construction), as this will allow a dynamic interpretation of cultural processes.